ANALISIS PENGARUH KETIMPANGAN GENDER TERHADAP PRODUKTIVITASTENAGA KERJA DI PROVINSI JAWA BARAT - Anisa Novita Sari (2022)
This study aims to determine the effect of the Gender Ratio on Life Expectancy (RLE), Gender Ratio on Mean Years of Schooling (RMYS), Gender Ratio on Labor Force Participation Rate (RLFPR), and Gender Ratio on Per Capita Expenditure (RPE). on labor productivity in all districts/cities of West Java Province. The sampling in this study used a saturated sampling technique in 27 districts/cities of West Java Province during 2015-2020 so that a total sample of 162 data was obtained from the Central Statistics Agency (BPS) of West Java. This study uses panel data analysis by combining time series data and cross section data. The results partially show that RLE and RLFPR have a significant positive effect on labor productivity, while RPE has a significant negative effect on labor productivity, and RMYS has no effect on labor productivity. The results of the study simultaneously showed that RLE, RMYS, RLFPR, and RPE had an effect on labor productivity.